REKONSTRUKSI IDENTITAS GENERASI ALFA DALAM TERANG KRISTUS DI TENGAH BUDAYA VALIDASI DIGITAL - Nofedin Waruwu (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2026)
This study examines the reconstruction of Generation Alpha’s identity in the light of Christ amid a culture of digital validation shaped by algorithmic mechanisms of social media. Generation Alpha grows within a digital ecosystem that normalizes the measurement of self-worth through quantitative metrics such as “likes,” “shares,” and “follows,” thereby reducing identity to a performative construct dependent upon public response. Employing a qualitative approach through literature review and theological-critical analysis, this research engages theological anthropology and Christology as its primary analytical frameworks. The findings indicate that the concept of imago Dei affirms the intrinsic value of human beings independent of social legitimation, while the Christological paradigm offers a relational and mission-oriented model of identity rooted in communion with the Father. Identity reconstruction in the light of Christ redirects the orientation of meaning from external validation toward participation in the life and mission of God, forming a resilient and transcendent identity amid the fluid dynamics of digital culture.